Photonic Platforms Using In‐Plane Optical Anisotropy of Tin (II) Selenide and Black Phosphorus. Issue 12 (7th October 2021) - Jo, Seong Soon; Wu, Changming; Zhu, Linghan; Yang, Li; Li, Mo; Jaramillo, Rafael
Abstract : Among layered and 2D semiconductors, there are many with substantial optical anisotropy within individual layers, including group‐IV monochalcogenides MX ( M  = Ge or Sn and X  = S or Se) and black phosphorous (bP). Recent work has suggested that the in‐plane crystal orientation in such materials can be switched (e.g., rotated through 90°) through an ultrafast, displacive (i.e., nondiffusive), nonthermal, and lower‐power mechanism by strong electric fields, due to in‐plane dielectric anisotropy. In theory, this represents a new mechanism for light‐controlling‐light in photonic integrated circuits (PICs). Herein, numerical device modeling is used to study device concepts based on switching the crystal orientation of SnSe and bP in PICs. Ring resonators and 1 × 2 switches with resonant conditions that change with the in‐plane crystal orientations SnSe and bP are simulated. The results are broadly applicable to 2D materials with ferroelectric and ferroelastic crystal structures including SnO, GeS, and GeSe. Abstract : Among layered and 2D semiconductors, there are many with substantial optical anisotropy within individual layers. Herein, numerical modeling is used to study device concepts based on switching ferroelastic domain patterns in triaxial SnSe and black phosphorous. The results are broadly applicable to using 2D materials with ferroelectric and ferroelastic crystal structures in photonic integrated circuits.